Pengembangan Sistem Informasi Data Rumah Rusak untuk Meningkatkan Efisiensi Penanganan Bencana - Khairani (Jurnal Sistem Komputer (SISKOM), 2022)
This study aims to develop and implement a Damaged House Data Information System to enhance the efficiency of disaster management efforts. The system is designed to streamline the collection, recording, and analysis of data on houses damaged by natural disasters, ensuring accurate and timely information for decision-makers. Key features include real-time data entry, geolocation tagging, damage assessment categorization, automated reporting, and a searchable database. By integrating mobile technology and cloud computing, the system allows field agents to upload data directly from disaster sites, providing immediate access to critical information. The research discusses the design, development, and deployment phases of the system, including technology selection, system architecture, and user interface considerations. The system is evaluated based on its impact on operational efficiency, data accuracy, and response times. The results indicate that the implementation of the Damaged House Data Information System leads to significant improvements in disaster response and recovery operations, reducing administrative burdens and enhancing the allocation of resources. The paper also addresses the challenges encountered during the development and deployment phases, along with the solutions implemented to ensure successful integration and user adoption.